2016
DOI: 10.1590/0104-6632.20160334s20150230
|View full text |Cite
|
Sign up to set email alerts
|

EFFICIENCY OF THE EARTHWORM Eisenia fetida UNDER THE EFFECT OF ORGANIC MATTER FOR BIOREMEDIATION OF SOILS CONTAMINATED WITH CADMIUM AND CHROMIUM

Abstract: -The use of earthworms to bioremediate soil results in decreasing the pollutant concentration through a bioaccumulation mechanism of the contaminants in the earthworm's body. The present work is an empirical study that was carried out on soils contaminated with chromium and cadmium. Organic matter in the amount of 5% and 9% of soil weight was added. Chromium and cadmium concentrations in soil and in the body of worms were measured at two time periods of 21 and 42 days. According to the results, increasing from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The reason for this may be that the pH of the earthworm gut environment is usually in the neutral to weakly alkaline range. The earthworms had higher chromium accumulation in acidic soil, which may have caused greater stress to the earthworms [ 64 ]. Hait and Tare’s research also showed that environmental factors, including pH, temperature, humidity, oxygen content, light, and organic matter in heavy-metal-contaminated soil, had an impact on the growth and survival of earthworms [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be that the pH of the earthworm gut environment is usually in the neutral to weakly alkaline range. The earthworms had higher chromium accumulation in acidic soil, which may have caused greater stress to the earthworms [ 64 ]. Hait and Tare’s research also showed that environmental factors, including pH, temperature, humidity, oxygen content, light, and organic matter in heavy-metal-contaminated soil, had an impact on the growth and survival of earthworms [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…[57,58] . Furthermore, it has been demonstrated in wet lab studies that Eisenia fetida's accumulation of lead II sulfate causes the protein Metallothionein to be expressed [59] . These findings are consistent with our ongoing in silico study, which has also demonstrated how the accumulation of the heavy metal, Lead II sulphate in Eisenia fetida and An.…”
Section: In Silico Docking Of Metal -Protein Dockingmentioning
confidence: 99%
“…However, data on OM impact on bioremediation are contradictory. In Mostafaii et al (2016) study was found that organic matter has no effect on bioremediation. Some studies have shown that an increase of OM in soil contaminated with heavy metals can reduce the damaging effects of the metals (Haghparast et al, 2013).…”
Section: Introductionmentioning
confidence: 98%